Pkm Peningkatan pengetahuan Lansia Tentang Manajemen Pencegahan Hipertensi Di Simpang Kubu Kabupaten Kampar - Kasumayanti, Erma; Hotna Siagian, Siti; Yuristin, Devina; Mayasari, Endang (Universitas Pahlawan Tuanku Tambusai, 2023)
Hypertension is an increase in systolic blood pressure of about 140 mm Hg or diastolic pressure of about 90 mm Hg. Hypertension is a problem that needs to be watched out for, because there are no specific signs of hypertension and some people still feel healthy to carry out their usual activities. This makes hypertension a silent killer. Hypertension occurs because it is influenced by risk factors. Risk factors that cause hypertension are age, gender, obesity, alcohol, genetics, stress, salt intake, smoking, patterns of physical activity, kidney disease and diabetes mellitus. The achievement of community service goals can be said to be very good (85%). There is an increase in the knowledge of the elderly and their families regarding hypertension, symptoms of hypertension, risk factors and prevention of hypertension. there is an increase of 80% of the elderly for routine blood pressure control using a digital tensimeter device and finally there is an increase in the knowledge of the elderly how to treat hypertension through progressive muscle relaxation techniques. The implementation of socialization activities to increase the knowledge of the elderly about the management of hypertension prevention in the Simpang Kubu village can run smoothly and obtain results according to the expected activity objectives. The purpose of this Community Service is measured. Achievement of material targets that have been planned can be said to be very good (85%). All material is delivered by a dedicated team for a limited time. The material that has been presented about hypertension includes the definition of hypertension, symptoms, risk factors and prevention of hypertension, explaining the stages of implementing hypertension management by carrying out routine blood pressure control and practicing progressive muscle relaxation activities and practiced by trainers and being asked to repeat one by one by the elderly and family members who come accompanied by cadres and trainers. Evaluation is carried out at the end of the activity. Evaluation is carried out after the assistance is carried out. The results obtained are an increase in knowledge and skills about increasing knowledge of the elderly and families regarding hypertension, how to carry out preventive management of hypertension by carrying out the stages of preventive management of hypertension in a routine way to monitor blood pressure, then being able to carry out progressive muscle relaxation techniques. Hypertension is an increase in systolic blood pressure of about 140 mm Hg or diastolic pressure of about 90 mm Hg. Hypertension is a problem that needs to be watched out for, because there are no specific signs of hypertension and some people still feel healthy to carry out their usual activities. This makes hypertension a silent killer. Hypertension occurs because it is influenced by risk factors. Risk factors that cause hypertension are age, gender, obesity, alcohol, genetics, stress, salt intake, smoking, patterns of physical activity, kidney disease and diabetes mellitus. The achievement of community service goals can be said to be very good (85%). There is an increase in the knowledge of the elderly and their families regarding hypertension, symptoms of hypertension, risk factors and prevention of hypertension. there is an increase of 80% of the elderly for routine blood pressure control using a digital tensimeter device and finally there is an increase in the knowledge of the elderly how to treat hypertension through progressive muscle relaxation techniques. The implementation of socialization activities to increase the knowledge of the elderly about the management of hypertension prevention in the Simpang Kubu village can run smoothly and obtain results according to the expected activity objectives. The purpose of this Community Service is measured. Achievement of material targets that have been planned can be said to be very good (85%). All material is delivered by a dedicated team for a limited time. The material that has been presented about hypertension includes the definition of hypertension, symptoms, risk factors and prevention of hypertension, explaining the stages of implementing hypertension management by carrying out routine blood pressure control and practicing progressive muscle relaxation activities and practiced by trainers and being asked to repeat one by one by the elderly and family members who come accompanied by cadres and trainers. Evaluation is carried out at the end of the activity. Evaluation is carried out after the assistance is carried out. The results obtained are an increase in knowledge and skills about increasing knowledge of the elderly and families regarding hypertension, how to carry out preventive management of hypertension by carrying out the stages of preventive management of hypertension in a routine way to monitor blood pressure, then being able to carry out progressive muscle relaxation techniques. Keywords: Elderly Knowledge, Hypertension